Developing and Validating a Model of Innovative Personality for High School Directors in Cambodia - Tonghor Hab; Sarom Mok; Chumnor Lek (Universitas Majalengka, 2026)
An innovative personality is central to developing innovative human capital, enhancing personal characteristics, and boosting national economies; consequently, schools play a vital role in building human resources that meet societal needs. This study aimed to validate a scale measuring the innovative personality of high school directors. A survey was conducted with 820 high school teachers across four Cambodian provinces to evaluate their perceptions of their principals’ task implementation. The 5-point Likert scale assessed school directors’ openness, leadership, and courage. Both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were employed. The EFA results demonstrated a robust three-dimensional structure with strong indicators, which was subsequently supported by the excellent model fit indices derived from the CFA. Further analysis revealed positive correlations across the subscales, confirming that convergent validity was achieved. The CFA fit indices demonstrated that the model fits the empirical data exceptionally well: X2/df = 2.32, p < 0.001, GFI = 0.99, NFI = 0.95, CFI = 0.97, TLI = 0.96, SRMR = 0.028, and RMSEA = 0.058. These findings indicate that the instrument is highly appropriate for the Cambodian secondary school context. Future research may extend the use of this scale to other educational levels to further examine its reliability and validity.